2023
DOI: 10.3389/fnins.2023.1206948
|View full text |Cite
|
Sign up to set email alerts
|

The role of pyroptosis in cognitive impairment

Abstract: Cognitive impairment is a major global disease, manifests as a decline in cognitive functioning and endangers the health of the population worldwide. The incidence of cognitive impairment has increased rapidly with an increasingly aging population. Although the mechanisms of cognitive impairment have partly been elucidated with the development of molecular biological technology, treatment methods are very limited. As a unique form of programmed cell death, pyroptosis is highly pro-inflammatory and is closely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Although the role and the mechanism of pyroptosis in cognitive dysfunction are not fully understood, studies have shown that P2X7R/NLRP3, NLRP3/caspase-1, NLRP3/caspase-1/gasdermin D (GSDMD) and other signaling pathways related to pyroptosis are involved in the occurrence and development of cognitive dysfunction with different causes [ 72 74 ]. In patients with cognitive impairment, the levels of pyroptosis signaling pathways are significantly upregulated, accompanied by release of a large number of inflammatory substances (such as IL-1β and IL-18), leading to an inflammatory response cascade that further causes damage to brain tissues [ 72 ].…”
Section: Effects Of Nlrp3 On Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role and the mechanism of pyroptosis in cognitive dysfunction are not fully understood, studies have shown that P2X7R/NLRP3, NLRP3/caspase-1, NLRP3/caspase-1/gasdermin D (GSDMD) and other signaling pathways related to pyroptosis are involved in the occurrence and development of cognitive dysfunction with different causes [ 72 74 ]. In patients with cognitive impairment, the levels of pyroptosis signaling pathways are significantly upregulated, accompanied by release of a large number of inflammatory substances (such as IL-1β and IL-18), leading to an inflammatory response cascade that further causes damage to brain tissues [ 72 ].…”
Section: Effects Of Nlrp3 On Pyroptosismentioning
confidence: 99%
“…Cerebrovascular disease is also a major cause of cognitive impairment. It includes acute ischemic stroke and chronic cerebral hypoperfusion (CCH) [ 72 ]. The acute ischemic stroke is caused by the sudden interruption or reduction of the local blood supply to the brain, which often occurs in conjunction with pre-existing microvascular and neurodegenerative changes, leading to disrupted energy supply, toxicity of excitatory glutamate, neuronal death, and cognitive dysfunction [ 94 ].…”
Section: Glial Activation Oxidative Stress and Neuroinflammationmentioning
confidence: 99%